Pengaruh Variabel Kontekstual Readiness for Change, Total Quality Management Practice, Komitmen Mutu, Mutu Produk terhadap Kinerja (Studi Perusahaan Tercatat pada Bursa Efek Indonesia) - Djaya, Yansor; Zain, Djumilah; Surachman, Surachman; Pujawan, I Nyoman (Jurnal Aplikasi Manajemen, 2011)
This research was aimed to develop and examine the relationship consistency of readiness for change contextual variable in analyzing the effect of Total Quality Management (TQM) practice on performance. Data collection used survey method by sending 748 questioners to senior manager of 393 listed companies at Indonesia Capital Market based on Indonesia Capital Market Directory year of 2008. Method of analysis used Sructural Equation Model (SEM) with company treated as unit of analysis. There were 108 data available for analysis. The research findings indicate for effectively implementation of TOM practice must be supported by high readiness for change of organization staff employee to create quality of outcome in terms of high product quality which increases performance. Managerial implication of this research stressing that managers should spend time to assess the readiness for TOM before implementing TOM practice in order to have optimal benefits and sustainability.